The Challenge of Reflecting ‘Social-Contextual’ Childhood Disability in Quantitative Research: A Narrative Review of the Literature - Ann Swift; Edurne Garcia Iriarte; Philip Curry (Scandinavian Journal of Disability Research, 2025)
For disability to be investigated quantitatively, it needs first to be defined and measured. While disability is now recognised as a complex social phenomenon, even in contemporary research, measures still often reflect the outdated medical model. For disabled children, the medical model is a particularly negative influence. Therefore, childhood disability research must find alternatives to traditional measures. In this narrative review of the literature, ‘social-contextual’ disability is identified as a basis for alternatives. Disabled children’s own reports of their lives echo these ideas, suggesting several themes with potential for measurement: experience of difference, material barriers, and other people’s behaviour. This review calls for innovation in survey content and administration to ensure children’s voices are heard, and theoretical frameworks that accommodate children with and without disabilities. Longitudinal study designs are recommended, and analytical techniques that allow meaningful groups to emerge from the data, rather than being imposed at the outset, are preferred.